A novel, simple and reliable method for the determination of hydronidone and its metabolites M3 and M4 in human plasma and urine by HPLC-MS/MS and its application to a pharmacokinetic study in health Chinese subjects - Zhang, Rui; Li, Peixia; Zhou, Jinping; Guo, Pengpeng; Liu, Yani; Shi, Shaojun (Analytical biochemistry, 2022)
In this study, a novel, simple and reliable high-performance liquid chromatography with tandem mass spetrometry method (HPLC-MS/MS) was developed for the determination of hydronidone and its metabolites M3 and M4 in human plasma and urine so as to study the clinical pharmacokinetics of hydronidone. By effectively inhibiting the proliferation of hepatic stellate cells (HSC), hydronidone can reduce collagen synthesis and curbs the process of liver fibrosis, and is currently in the stage of clinical research for anti-liver fibrosis. Hydronidone and its metabolites M3, M4 were extracted from human plasma by protein precipitation, and the urine samples were directly diluted with acetonitrile and analyzed by HPLC-MS/MS. The quantification ranges in plasma were 1.00–1000 ng/mL, 2.00–2000 ng/mL and 4.00–4000 ng/mL, respectively and in urine were 10.0–2000 ng/L, 100–25000 ng/L and 300–75000 ng/L, respectively. Coefficients of variation of less than 15% between intraday and interday accuracy and precision values were observed for hydronidone, M3 and M4. The S/N (signal-to-noise ratio) of the analyte in each Low limit of quantification sample in the analytical batch was greater than 5, indicating good sensitivity. The recovery rates were above 50% for all analytes. The parameters such as linearity, selectivity, lower precision, accuracy, recovery, stability and matrix effects were validated by the methodology and met the requirements specified by the FDA and the European Medicines Agency. The method has been successfully applied to the pharmacokinetics of hydronidone and its metabolites M3 and M4 in healthy Chinese volunteers. [Display omitted] •HPLC/MS/MS method for hydronidone and its metabolites M3 and M4 was established for the first time.•The method is accurate and reliable for determination of hydronidone and its metabolites in human plasma and urine samples.•The method has been successfully applied in pharmacokinetic study of healthy volunteers.